Persepsi mahasiswa terhadap lingkungan pembelajaran di Universitas Sam Ratulangi Manado - Tompodung, Linda M. (eBiomedik, 2017)
Abstract: Learning environment in any medical school is an important factor to determine the quality and success of curriculum. Students’ experience about their learning environment in medical education is related to their achievement, satisfaction, and success. It is important to get reguler feedback from the students on how they experience their learning environment as basis of strategic planning for futher improvement. This study was aimed to assess the educational environment of Sam Ratulangi University (Unsrat) undergraduate medical program based on the students’ perspection and also to identify the difference in perception between genders. This was an analytical study with a cross-sectional design conducted in October 2016 among undergraduate students of academic year 2016/2017. Data about the learning environment were obtained by using questionnaire of Dundee Ready Educational Environment Measure (DREEM) and further analyzed with the Mann-Whitney test to identify the significance between genders. The total DREEM score indicated more positive than negative perception with rooms of improvement (127/200). The scores for all the five subscales of DREEM indicated a more positive perception. The overall mean DREEM score of the females (128,16) was higher compared to males (126,13) but not statistically significant. Conclusion: The medical students of Sam Ratulangi University showed a positive perception about their undergraduate educational environment. Continuous quality improvement and innovation are essentially needed.Keywords: educational environment, medical education, DREEM Abstrak: Lingkungan pembelajaran merupakan salah satu faktor penting dalam menentukan kualitas dan keberhasilan kurikulum pendidikan kedokteran. Persepsi mahasiswa terhadap lingkungan pembelajaran terbukti memengaruhi prestasi, kepuasan dan kesuksesan mahasiswa. Penting untuk mendapatkan umpan balik berkala dari mahasiswa tentang yang mereka rasakan terkait lingkungan pembelajaran sebagai dasar strategi perencanaan untuk peningkatan di masa depan. Penelitian ini bertujuan untuk menilai lingkungan pembelajaran melalui persepsi mahasiswa dan mengidentifikasi perbedaan jenis kelamin di Fakultas kedokteran Universitas Sam Ratulangi (Unsrat) Manado. Jenis penelitian ialah analitik dengan desain potong lintang, dilakukan pada bulan Oktober 2016 terhadap mahasiswa TA 2016/2017. Data persepsi terhadap lingkungan pembelajaran didapat dari kuesioner Dundee Ready Educational Environment Measure (DREEM). Analisis data dilakukan menggunakan uji Mann-Whitney untuk mengidentifikasi perbedaan antara jenis kelamin. Hasil nilai total DREEM menunjukkan lingkungan yang lebih positif daripada negatif dengan ruang untuk perbaikan (127/200). Nilai skor dari kelima subskala DREEM mengindikasikan persepsi yang lebih positif. Nilai total rerata DREEM mahasiswa perempuan (128,16) lebih tinggi dibandingkan dengan laki-laki (126,13) namun tidak terdapat perbedaan bermakna antara persepsi terhadap lingkungan pembelajaran berdasarkan jenis kelamin. Simpulan: Mahasiswa kedokteran Unsrat memiliki persepsi positif terhadap lingkungan pembelajaran. Peningkatan kualitas secara berkala dan inovasi merupakan hal yang esensial dalam pendidikaan kedokteran.Kata kunci: lingkungan pembelajaran, pendidikan kedokteran, DREEM